2017
DOI: 10.1039/c7mb00094d
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and analysis of the lncRNA–miRNA–mRNA network based on competitive endogenous RNA reveal functional lncRNAs in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease with an unknown etiology, occurring in approximately 1.0% of general population. More and more studies have suggested that long non-coding RNAs (lncRNAs) could play important roles in various biological processes and be associated with the pathogenesis of different kinds of diseases including RA. Although a large number of lncRNAs have been found, our knowledge of their function and physiological/pathological significance is still in its infancy. In order to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
84
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 58 publications
0
84
0
Order By: Relevance
“…Furthermore, miR‐125b‐mediated mitochondrial apoptosis pathways also play important roles in chemotherapy drug‐induced apoptosis . The competitive endogenous RNA (ceRNA) theory for miRNA and lncRNA is currently widely accepted . To date, the role of LINC00152 in ovarian cancer is unclear, and whether LINC00152 achieves its role in cancer through the miR‐125b‐mediated mitochondrial pathway remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR‐125b‐mediated mitochondrial apoptosis pathways also play important roles in chemotherapy drug‐induced apoptosis . The competitive endogenous RNA (ceRNA) theory for miRNA and lncRNA is currently widely accepted . To date, the role of LINC00152 in ovarian cancer is unclear, and whether LINC00152 achieves its role in cancer through the miR‐125b‐mediated mitochondrial pathway remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Under this ceRNA network, the lncRNAs and mRNAs are connected by their common target miRNAs [30]. In recent years, several studies have explored the underlying molecular mechanisms based on the ceRNA network in some diseases, such as breast cancer [32], ischemic stroke [33], and rheumatoid arthritis [34]. To identify lncRNAs significantly associated with POAG, in this study, the mRNA and lncRNA expression profiles of POAG patients were first used and combined with miRNA-target interactions to create a ceRNA network and to investigate the potential implications of these lncRNAs in the development of POAG.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs such as lncRNAs and miRNAs have been proven to participate in the regulation of gene expression through competition for endogenous RNA networks with mRNA (Kartha & Subbaya 2014). The interaction between these two ncRNAs plays an important role in tumor development (Jiang et al 2017;Wu et al 2016). At present, the specific molecular mechanism of the interaction between lncRNA and miRNA is speculated to be one of two possibilities:1. because lncRNAs and mRNAs have a similar structure, a miRNA can specifically bind to its 3' UTR and down-regulate lncRNA expression through a mechanism similar to that of mRNA regulation (Shi et al 2013); or 2. studies have confirmed that lncRNAs can competitively target miRNAs to inhibit the expression of miRNAs, thereby reducing their inhibitory effect on target genes (Salmena et al 2011).…”
Section: Discussionmentioning
confidence: 99%